Sexual Dysfunction in Puerto Rican Women with Inflammatory Bowel Disease - Pérez-Rodríguez, Paola K.; Marqués-Lespier, Juan M.; Ortiz, Adriana; Emanuelli, Natalie I.; Viñas-Joy, Grace M.; Torres, Esther A. (Puerto Rico Health Sciences Journal, 2020)
Objective: Inflammatory bowel disease (IBD) negatively impacts quality of life–related issues including intimacy, body image, and sexual activity. Sexual dysfunction in patients with IBD is often unrecognized. In this study, we aimed to describe sexual function in Puerto Rican women with IBD. Methods: We conducted a cross-sectional study of women with IBD at the University of Puerto Rico Center for IBD. Patients were invited to anonymously complete the validated Spanish version of the Female Sexual Function Index (FSFI) questionnaire. On this 36-point scale, a score of 26.55 or less is defined as sexual dysfunction. Data were analyzed by diagnosis, presence of an ostomy, and age, using descriptive statistics, ANOVA, Student’s t test, and logistic regression. Results: One hundred women completed the FSFI questionnaire, with subjects having Crohn’s disease (CD) outnumbering those having ulcerative colitis (UC) 2:1. The mean sexual function score was 21.92 (95% CI: 20.08–23.76). No statistical difference was observed in total FSFI scores between subjects with CD and UC (p = 0.084) and those with an ostomy (p = 0.891). Sexual function decreased with age (p = 0.001). The domains of excitation, lubrication, orgasm, and satisfaction were the most negatively affected (p<0.05) by increasing age. Multivariate analysis confirmed the effect of age on excitation, lubrication, orgasm, and pain. Conclusion: Our study showed sexual dysfunction to be present in this sample of Puerto Rican Hispanic women with IBD. Physicians treating patients with IBD need to be aware of these findings to explore the concerns of individuals with this disease and develop strategies to address those concerns.